2009
DOI: 10.1088/1741-2560/6/2/026003
|View full text |Cite
|
Sign up to set email alerts
|

Overlap and refractory effects in a brain–computer interface speller based on the visual P300 event-related potential

Abstract: We reveal the presence of refractory and overlap effects in the event-related potentials in visual P300 speller datasets, and we show their negative impact on the performance of the system. This finding has important implications for how to encode the letters that can be selected for communication. However, we show that such effects are dependent on stimulus parameters: an alternative stimulus type based on apparent motion suffers less from the refractory effects and leads to an improved letter prediction perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
103
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(104 citation statements)
references
References 22 publications
0
103
0
1
Order By: Relevance
“…Since then, a range of improvements has been proposed to the original interface [24][25][26] and the EEG signal processing techniques [27,28]. Recently, a large group study by Guger et al [29] reported that in 81 healthy users , 89% were able to successfully use a P3-based BCI for spelling, with accuracies of 80% and above.…”
Section: P3-based Bcismentioning
confidence: 99%
“…Since then, a range of improvements has been proposed to the original interface [24][25][26] and the EEG signal processing techniques [27,28]. Recently, a large group study by Guger et al [29] reported that in 81 healthy users , 89% were able to successfully use a P3-based BCI for spelling, with accuracies of 80% and above.…”
Section: P3-based Bcismentioning
confidence: 99%
“…The computer identifies the attended item as the intersection of the row and column that elicited the largest P300. The RCP has been tested in various configurations to achieve efficient communication that is practical for in-home use Lenhardt et al, 2008;; the paradigm itself has been modified (Guger et al, 2009;Hong et al, 2009;Martens et al, 2009;Salvaris & Sepulveda, 2009;Takano et al, 2009). Unfortunately, none of such alternative paradigms substantially improves P300-based BCI performance.…”
Section: Treatment Of Impaired Communicationmentioning
confidence: 99%
“…Over the last few years there has been a healthy interest in trying to improve P300-based BCIs through modifications of the protocol used [1]- [3]. These modification come from trying to mitigate the temporal limitations of the P300 signal [1] or simply by observing the possible effects of the alterations to the visual makeup of the protocol [2], [3].…”
Section: Introductionmentioning
confidence: 99%
“…These modification come from trying to mitigate the temporal limitations of the P300 signal [1] or simply by observing the possible effects of the alterations to the visual makeup of the protocol [2], [3]. For example, in [3] a number of modifications were made to the visual properties of a P300 matrix speller, including, the size of the letters, the distance between the letters and the colours used.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation